Contribution of neuraminidase 3 to the differentiation of induced regulatory T cells. (22nd December 2017) - Kaminuma, Osamu; Katoh, Shigeki; Miyagi, Taeko; Watanabe, Nobumasa; Kitamura, Noriko; Nishimura, Tomoe; Saeki, Mayumi; Mori, Akio; Hiroi, Takachika
Abstract : Neuraminidase family enzymes that hydrolyze the terminal sialic acid linkage in biomolecules are involved in various immune responses. We previously showed that Th1 and Th2 cells differentially express several neuraminidases. Herein, the expression of neuraminidases in induced regulatory T (iTreg) cells was investigated in comparison with that in other T‐cell subsets. Contrary to the tendency toward higher neuraminidase 1 mRNA expression in in vitro‐differentiated Th2 cells, compared to Th1, Th17 and iTreg cells, we observed significantly higher expression of neuraminidase 3 (Neu3) in iTreg cells. Furthermore, the expression of Neu3 in FoxP3 + CD62L − spleen cells was higher than that in FoxP3 + CD62L + and FoxP3 − cells. Lentiviral expression of Neu3 in naïve CD4 + T cells during the stimulation culture led to upregulation of FoxP3 expression. On the basis of these findings, we conclude that Neu3 contributes to the differentiation of iTreg cells by upregulation of FoxP3. Abstract : The expression of neuraminidase 3 (Neu3) was significantly higher in Treg cells than in Th1, Th2 and Th17 cells. Activated Treg cells expressed higher level Neu3. Neu3 enhanced FoxP3 expression in T cells.